CONODONT BIOSTRATIGRAPHY OF UPPER DEVONIAN TEPHRA BEARING DEPOSITS IN THE İSTANBUL-ZONGULDAK TERRANE, NW TURKEY: INSIGHTS ON THE KELLWASSER EVENTS (Rivista italiana di Paleontologia e Stratigrafia, 2024)
New evidence for a biostratigraphic assessment of the limestone succession comprising K‐bentonite levels exposed in the Yılanlı Formation of the Istanbul-Zonguldak Terrane are provided from conodonts at the Gavurpınarı quarry in Bartın area (NW Turkey). The succession depicts a shallow marine, nearshore facies setting that comprises rare and low diversity conodont associations mainly exemplified by the species of Ctenopolygnathus, Icriodus and Polygnathus. Conodont faunas from the lower part of the section are of late Frasnian age, including the taxa Icriodus subterminus Youngquist, 1947, Polygnathus aff. xylus Stauffer, 1940, Icriodus iowaensis iowaensis Youngquist & Peterson, 1947 and Ctenopolygnathus brevilaminus Branson & Mehl, 1934, and the upper part is assigned to early Famennian marked by the first appearance of Icriodus cornutus Sannemann, 1955. The local biostratigraphic framework of the Yılanlı Formation is correlated with the upper Frasnian Lower rhenana to the lower Famennian Middle triangularis standard conodont zonations. Considering the described species, the Frasnian-Famennian boundary corresponds to a slight change in conodont fauna and is assigned within the local Icriodus iowaensis iowaensis Zone. Accordingly, the novel K-bentonite age data potentially indicates the evidence for the Kellwasser events in northern Turkey, improving paleogeographic correlations of the Istanbul-Zonguldak Terrane with other terranes in Laurasia and Peri-Gondwana.